Investment timing for new business ventures - George W. Blazenko; Andrey D. Pavlov (The Journal of Entrepreneurial Finance (JEF), 2010)
A key requirement for the start of many entrepreneurial businesses is private equity or venture capital financing. In the traditional approach to entrepreneurial investment analysis, an entrepreneur starts a new venture and a venture capitalist finances the new venture when business return exceeds the financial opportunity cost for comparable risk the cost of capital for the new venture. The real options literature recommends that entrepreneurs delay business start due to investment irreversibility until business return reaches a threshold greater than the cost of capital. In this paper, we show that for new ventures with modest earnings volatility, an entrepreneur starts his/her business before return exceeds the cost of capital. We identify the circumstances in which the cost of capital is an unduly conservative return benchmark for the start of a new business and discuss the empirical implications of our findings.
Keywords: 650; new ventures; business start; corporate investment